Antecedents of Maternal Rejection Across Cultures: An Examination of Child Characteristics. (May 2020) - Son, Heimi; Lee, Young Ae; Ahn, Dong Hyun; Doan, Stacey N.; Ha, Eun Hye; Choi, Yun Seo
Maternal rejection may be associated with individual child characteristics. This relationship may vary across cultures. This study aimed to identify group differences in maternal rejection as well as child characteristics. We also explored the moderating role of culture in influencing the relations between child characteristics and maternal rejection. In total, 153 mothers with a child aged 3 to 6 years participated in the survey. Participants were from the East Coast of the United States ( N = 48); Seoul, Korea ( N = 65); and Japan (Tokyo and Saitama) ( N = 40). American mothers perceived their children to be more active and extroverted than did Korean mothers, who perceived their children to be better at controlling their behavior than American and Japanese mothers. American mothers reported significantly higher levels of their children's behavior problems than Korean and Japanese mothers. It was observed that culture moderated the relations between child factors (e.g., effortful control and internalizing problems) and maternal rejection. These findings suggest that culture influences the association between child characteristics (temperament and behavior) and maternal rejection.